Specyfika funkcjonowania form adresatywnych w językach polskim i ukraińskim (uwagi wstępne) - Fedoriuk, Maryna (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The paper presents the main features of the Polish and Ukrainian traditions of using forms of addresses. The main cultural and language differences are shown as determined by the potential of the Polish and Ukrainian systems of addressing and pragmatic factors.